A word of caution for Pakistani drug authorities regarding enhanced availability of dietary supplements: - - Esha Rafique; Usama Memon; Muhammad Adil Obaid (Journal of the Pakistan Medical Association, 2022)
As my manuscript is the letter to the editor therefor it has no abstract.